2011
DOI: 10.3109/08880018.2011.572144
|View full text |Cite
|
Sign up to set email alerts
|

Complications of β-Thalassemia Intermedia in Iran During 1996–2010 (Single-Center Study)

Abstract: Patients with thalassemia intermedia (TI) experience many complications, of which the incidence varies greatly among cases. Considering the high prevalence of thalassemia in Iran, the study was carried out to determine the frequency of TI complications in Iranian patients and to find possible risk factors for each of them. Using the sampling method of "census," the authors included 153 patients who were seen in their tertiary hematology clinic with the diagnosis of TI during 1996-2010; an analytical cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
3
13
1
Order By: Relevance
“…Nonetheless, and similar to patients with Class 4 pulmonary hypertension attributed to chronic thromboembolic disease, hypercoagulability can play a major role in the cause of PAH, where thrombi may be present in both the small distal pulmonary arteries and the proximal elastic pulmonary arteries. 7 The association of splenectomy and older age with increased PAH risk in our study echoes previous reports 18,19,22,24,25,33,35,[39][40][41] and further supports the latter hypothesis. Abnormalities of platelets and hemolyzed red blood cells are believed to be the key factors causing hypercoagulability and subsequent thrombotic events in β-thalassemia; especially older, splenectomized, β-thalassemia intermedia patients.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Nonetheless, and similar to patients with Class 4 pulmonary hypertension attributed to chronic thromboembolic disease, hypercoagulability can play a major role in the cause of PAH, where thrombi may be present in both the small distal pulmonary arteries and the proximal elastic pulmonary arteries. 7 The association of splenectomy and older age with increased PAH risk in our study echoes previous reports 18,19,22,24,25,33,35,[39][40][41] and further supports the latter hypothesis. Abnormalities of platelets and hemolyzed red blood cells are believed to be the key factors causing hypercoagulability and subsequent thrombotic events in β-thalassemia; especially older, splenectomized, β-thalassemia intermedia patients.…”
Section: Discussionsupporting
confidence: 81%
“…Owing to the systematic approach undertaken in our study, we believe that estimates presented in this report are more likely representative of the true PAH prevalence in patients with β-thalassemia. Our study echoed previous reports demonstrating that the prevalence of PAH is higher in β-thalassemia intermedia than β-thalassemia major [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] but did not observe the previously reported female predominance. 34,35 The correlation between sPAP as estimated on echocardiography and as measured on right heart catheterization was only moderately good in our study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In contrary, a cohort study of TI patients has shown terrifying evidence that β‐TI patients representing NTDT had a much higher incidence of several thalassemia related complications compared to β‐TM who were well‐treated . This finding was consistent with several studies from Mediterranean countries, the Middle East, and Indian subcontinents . However, there were limited data of the prevalence of thalassemia related complications in NTDT from Southeast Asian populations and none was a prospective study.…”
Section: Introductionsupporting
confidence: 68%